Análise da escoabilidade de pós - Campos, Milene Minniti de (2012)
There are many industries which use powders somewhere in their production process, such as: food, pharmaceuticals, ceramics, cement and fertilizer industries. The knowledge of properties associated with the flowability of these materials is important, since the characteristics of the powders can go through amendments in processing. Thus, the evaluation of indexes of flowability and the identification of main factors which influence the powders flowability play an important role in the operation and design of industrial devices. The objective of this study was to evaluate the flowability properties of organic and inorganic powders, as well as analyze which factors interfered in these properties. The organic materials were represented by whole and skim milk powders, while alumina and ceramic powder were selected for the assessment of inorganic materials. The physical characterizations carried out were: display materials morphology at SEM (Scanning Electron Microscopy), size distribution, particle density, initial moisture content, aerated bulk density and tapped bulk density. The measured materials flowability properties were: angle of internal friction, effective angle of internal friction, angle of wall (galvanized steel) friction and flow index, all of them determined by Jenike's direct shear cell, Hausner ratio obtained from the values of tapped and aerated bulk densities; angle of repose, determined through the dropping of powder in an acrylic surface. In general, the results obtained, considering all methodologies employed for the determination of materials flowability, demonstrated that alumina, ceramic powder and whole milk powder, if compared to skim milk powder, presented lower indexes of flowability. If these materials were stored in silos made of galvanized steel, alumina and ceramic powder flowability would be more difficult than that of skim and whole milk powders. Thus, the results showed that the material physical properties interfere in powders flowability. The skim milk powder flowed more easily than whole milk powder, because higher fat content and smaller average particle size of whole milk powder decreased the flowability of this material in comparison to the skim milk powder. Likewise, despite they have similar composition, alumina presented lower flowability that ceramic powder, because this powder had larger average particle size and the powder presented fewer agglomerated particles.